Russian-speaking Journalists of Foreign Media about the Media Image of the Chechen Republic - A. Yu. Evseev (Управленческое консультирование)
The article deals with theoretical aspects of the media image of the state/region and its components: image, conditions for the distribution of information flows; studied the group sociodynamics of the life of the population from the point of view of foreign journalists. To do this, a survey was conducted of foreign media employees who studied at advanced training courses at the North-Western Institute of the RANEPA under the President of the Russian Federation.The author notes that the most important characteristic identified by the theoretical and practical research pathway is the behavioral actions of people who are directly related to the object: these include journalists who form the information flow from the point of view of creating a certain media image.Particular attention is paid to the ratio of the information available to journalists about life in Chechnya and their ideas about the modern situation in the republic. The ratio of negative, neutral and positive tonality of submitting information about the Chechen Republic to the media was revealed.The analysis demonstrates that the media policy of the republic, aimed at the external audience for the country, needs to be adjusted. As recommendations, the author writes that the reflection of the identity of the region, its traditions and culture can form a significant part of the media image toolkit.